2021
DOI: 10.1126/scitranslmed.abb0130
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and immunotherapy converge on elimination of tumor-promoting erythroid progenitor cells through adaptive immunity

Abstract: Tumor-induced CD45−Ter119+CD71+ erythroid progenitor cells, termed “Ter cells,” promote tumor progression by secreting artemin (ARTN), a neurotrophic peptide that activates REarranged during Transfection (RET) signaling. We demonstrate that both local tumor ionizing radiation (IR) and anti–programmed death ligand 1 (PD-L1) treatment decreased tumor-induced Ter cell abundance in the mouse spleen and ARTN secretion outside the irradiation field in an interferon- and CD8+ T cell–dependent manner. Recombinant eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 67 publications
0
41
0
Order By: Relevance
“…Many previous studies have shown that the immune system plays an important role in mediating the antitumor effects of RT [35,36]. For instance, RT can activate the antitumor immune effect by inducing the maturation of dendritic cells and enhancing the activation of T cells [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have shown that the immune system plays an important role in mediating the antitumor effects of RT [35,36]. For instance, RT can activate the antitumor immune effect by inducing the maturation of dendritic cells and enhancing the activation of T cells [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that immunomodulatory properties are strong in early-stage CD45 + CECs in contrast to more mature CD45 − CECs that lack these capacities 9 , 10 , 17 , 44 . However, other studies also reported the immunomodulatory role of CD45 − CECs 41 , 45 , which suggests that CD45 alone may not be a reliable marker of immunosuppressive CECs. Here, we showed that human CECs acquire immunomodulatory properties during erythroid differentiation and are the most potent in an early stage characterized by the CD71 high CD235a mid phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies demonstrated that immunomodulatory properties are strong in early-stage CD45 + CECs in contrast to more mature CD45 -CECs that lack these capacities 9,10,17,43 . However, other studies also reported the immunomodulatory role of CD45 -CECs 40,44 , which suggests that CD45 alone may not be a reliable marker of immunosuppressive CECs. Here, we showed that human CECs acquire immunomodulatory properties during erythroid differentiation and are the most potent in an early stage characterized by the CD71 high CD235a mid phenotype.…”
Section: Discussionmentioning
confidence: 96%